PENINGKATAN KOMPETENSI PENYULUH PERTANIAN DI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) DENGAN PEMANFAATAN MEDIA KOMUNIKASI - Eni Kustanti; Agus Rusmana; Purwanti Hadisiwi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
Efforts to improve the competency of agricultural extension workers have been carried out through education and training by the Agency for Agricultural Extension and Human Resources Development. Improving the competence of agriculture extension workers through the utilization of communication media has not been used intensively by the government. The purpose of this study is to know the level of influence of communication media utilization on the competence of agricultural extension workers. The study was used a quantitative approach through an online survey of 203 agricultural extension workers at the Assessment Institute for Agricultural Technology from 33 provinces. The results showed that the utilization of communication media and characteristics of individual had a significant effect on the competence of agricultural extension workers. Environmental support factors have a significant effect on the utilization of communication media and have an indirect effect on the competence of agricultural extension workers. The most and significant influence on the competence of agricultural extension comes from the utilization of communication media which is 4.38. Meanwhile, the significant factor affecting the utilization of communication media is only in the form of environmental support of 0.34. Therefore, to improve the competence of agricultural extension workers, utilization of communication media in the dissemination of agricultural information should be increased. Furthermore, to increase the utilization of communication media in the dissemination of agricultural information, the environmental support of extension activities, such as literacy training on the use of variation communication media, should be improved.